The Interplay of Sex Steroids, the Immune Response, and the Intestinal Microbiota. Issue 9 (September 2021) - Pace, Fernanda; Watnick, Paula I.
Abstract : The role of sex steroids in mammalian maturation is well established. Recently, it has been increasingly appreciated that sex steroids also play an important role in the propensity of adults to develop a myriad of diseases. The exposure and responsiveness of tissues to sex steroids varies among individuals and between the sexes, and this has been correlated with gender-specific differences in the composition of the intestinal microbiota and in susceptibility to metabolic, autoimmune, and neoplastic diseases. Here we focus on recent studies that demonstrate an interplay between sex steroids, the intestinal immune response, and the intestinal microbiota. While correlations between biological sex, the intestinal innate immune response, intestinal inflammation, and intestinal microbiota have been established, many gaps in our knowledge prevent the emergence of an overarching model for this complex interaction. Such a model could aid in the development of prebiotic, probiotic, or synthetic therapeutics that decrease the risk of autoimmune, metabolic, neoplastic, and infectious diseases of the intestine and mitigate the particular health risks faced by individuals receiving sex steroid treatment. Highlights: Sex steroids modulate intestinal inflammation. The intestinal microbiota is shaped by sex steroids. The intestinal microbiota alters circulating levels of sex steroids. Sex steroids impact bacterial physiology through direct interactions.